2000
DOI: 10.3758/bf03198420
|View full text |Cite
|
Sign up to set email alerts
|

Part—set cuing of order information: Implications for associative theories of serial order memory

Abstract: In three experiments, the effect of cuing, at the point of test, on memory for order and/or position was investigated, Experiment 1 used a partial reconstruction of order task to demonstrate a mnemonic benefit of part-set cuing at the time of test; this result is used to argue that people may commonly use interitem associative information, rather than just position information, to help them remember serial order. Experiment 2 replicated these findings and simultaneously demonstrated the mnemonic detriment that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
72
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 43 publications
4
72
2
Order By: Relevance
“…Significant inhibitory effects of part-set cueing have been found for shopping lists (Bovee, Fitz, Yehl, & Kelley, 2009) and expository text (Fritz & Morris, 2015) but for other stimuli, such as chess board layouts, uncategorised word lists, serial order, and complex scenes, partset cues have been found to have either no effect or a facilitative effect on subsequent recall (Cole, Reysen, & Kelley, 2013;Fritz & Morris, 2015;Serra & Nairne, 2000;Slamecka, 1969;Watkins, Schwartz, & Lane, 1984). If the inhibitory effect of part-set cueing is assumed to arise from either the disruption of a preferred retrieval strategy or response competition during retrieval (e.g.…”
Section: Autobiographical Recallmentioning
confidence: 99%
“…Significant inhibitory effects of part-set cueing have been found for shopping lists (Bovee, Fitz, Yehl, & Kelley, 2009) and expository text (Fritz & Morris, 2015) but for other stimuli, such as chess board layouts, uncategorised word lists, serial order, and complex scenes, partset cues have been found to have either no effect or a facilitative effect on subsequent recall (Cole, Reysen, & Kelley, 2013;Fritz & Morris, 2015;Serra & Nairne, 2000;Slamecka, 1969;Watkins, Schwartz, & Lane, 1984). If the inhibitory effect of part-set cueing is assumed to arise from either the disruption of a preferred retrieval strategy or response competition during retrieval (e.g.…”
Section: Autobiographical Recallmentioning
confidence: 99%
“…Juxtaposed against the vast body of evidence accumulated against chaining models is a smaller body of evidence in support of chaining. Serra and Nairne (2000) investigated the role of item-to-item associations in memory for serial order using a part-set cuing task. In this task participants performed serial reconstruction on eightitem lists.…”
Section: Chaining Modelsmentioning
confidence: 99%
“…Kahana and Caplan (2002) have shown that recall of item n in a serial list is better if it is cued with the immediately preceding item (n 1) than with the immediately following item (n 1). Serra and Nairne (2000) found that participants were better able to reconstruct the serial positions of some list items if other list items were placed in their appropriate presentation positions at test. Thus, rather than producing interference, the recall of item n 1 might enhance the recall of item n, and other nearby neighbors, and only impair the recovery of items occurring at more temporally distant positions in the list.…”
mentioning
confidence: 96%